Wishful Thinking in Strategic Environments - Yildiz, Muhamet (Review of Economic Studies, 2007)
Abstract. Towards developing a theory of systematic biases about strategies, I analyze strategic implications of a particular bias: wishful thinking about the strategies. Considering canonical state spaces for strategic uncertainty, I identify a player as a wishful thinker at a state if she hopes to enjoy the highest payoff that is consistent with her information about the others’ strategies at that state. I develop a straightforward elimination process that characterizes the strategy profiles that are consistent with wishful thinking, mutual knowledge of wishful thinking, and so on. Every pure-strategy Nash equilibrium is consistent with common knowledge of wishful thinking. For generic two-person games, I further show that the pure Nash equilibrium strategies are the only strategies that are consistent with common knowledge of wishful thinking, providing an unusual epistemic characterization for equilibrium strategies. I also investigate the strategic implications of rationality and ex-post optimism, the situation in which a player’s expected payoff weakly exceeds her actual payoff. I show that these strategic implications are generically identical to those of wishful thinking whenever each player’s payoff is monotone in others ’ strategies.